River-groundwater transformation and ecological effects in the Tuwei River watershed - Jinxuan WANG; Yi WANG; Fan GAO; Xuanming ZHANG; Zhitong MA; Fan YANG (Shuiwen dizhi gongcheng dizhi)
The Tuwei River, an important tributary of the Yellow River, located in the eastern Jiziwan region exhibits a close hydraulic connection between atmospheric precipitation, groundwater, and river-lake water in the watershed. This connection influences the evolution, stability and safety of the watershed ecological pattern. Based on the geological, geomorphological and hydrogeological conditions, and the water transformation between atmospheric precipitation, groundwater, and river-lake water (hereinafter referred to as three-water) in the Tuwei River, this study examined the characteristics of the three-water transformation and their ecological effects using field investigation, dynamic observation, sensing interpretation, base flow analysis, and statistical analysis. Under the control of geological and geomorphological conditions and the three-water transformation, the watershed can be spatially divided into lakes-shrub-grass-tree wet environment ecosystem, grass-shrub-tree-sand dry environment ecosystem, dwarf sparse forest-grass dry environment ecosystem, farmland-tree wet environment ecosystem, and riparian wet environment ecosystem. Since the 1990s, the vegetation coverage of the watershed has increased, while the groundwater levels have dropped, the river base flow has decreased, and the lake wetland has shown a decreasing trend. The formation and evolution of the watershed ecological pattern is the result of a combination of natural factors and human activities. The geological and geomorphological conditions control the watershed ecological pattern, and the hydrological cycle characteristics control the evolution direction and spatiotemporal variation trend of the watershed ecological pattern. Human activities have greatly changed the original ecological pattern and dominated the direction and intensity of the contemporary ecological pattern evolution. The safety and stability of the watershed ecological pattern are highly dependent on water resources. Maintaining hydrological connectivity, enhancing the intensity of three-water transformation, and ensuring the groundwater level in the desert area within the range of 1.5～5 m are crucial to the health of the ecosystem in the area. Based on the one-way three-water transformation characteristics in the Tuwei River, the definition of the riparian zone was proposed. The riparian zone is the source and sink of water flow, material flow, energy flow, and information flow in the watershed, and plays the role of an ecological corridor. The ecological function of the riparian zone has an indicative effect on the status of the watershed ecological environment and can be used as one of the important indicators for the assessment of the watershed ecological system. These findings support the protection and governance of ecological environments for the Jiziwan region of the Yellow River and similar watersheds.